The Arabic Language’s Role in Determining Sunnah Corruption - Muhammad Muthi`ul Haqq Bin Fatah Yasin; Basri Bin Ibrahim (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
Sunnah means words, actions, agreements and attributes referred to Rasulullah S.A.W. Authentic understanding of Sunnah needs a careful examination of meaning in literal and contextual aspects. Literal meaning can be recognized through Sunnah text without referring to reason of hadith revelation. Literal understanding of Sunnah text needs high Arabic language skills to avoid mistakes in understanding Sunnah text and cause fraud upon Rasulullah S.A.W. From practical aspect, understanding literal meaning of Sunnah text needs mastery of Arabic language from three aspects which are meaning of words, meaning based on the word`s position in the sentence and meaning of words according to situation. In this study, the researcher focused on the roles of Arabic language in determination of corrupted understandings of Sunnah mentioned in books of previous scholars caused by mistakes from Arabic language aspect whether intended or not. This study aims to examine the roles of Arabic language in determination of Sunnah corruption. Method implemented in this study is qualitative method. Data was obtained based on document analysis by focusing on books related to Sunnah, Tauhid and Fiqh. Textual examination meanwhile was taken from books of Arabic language discipline related to knowledge of Saraf, Nahu and Balaghah. This study found that the main cause of corrupted Sunnah understandings to appear is due to mistakes in understanding Sunnah text from Arabic language aspect. From aspect of effect, ignorance of Arabic language in understanding Sunnah text causes the meaning to be wrongly concluded from the exact meaning and becomes the basis for corrupted understandings. In conclusion, Arabic language skills are a need to determine mistakes occurring in understanding of Sunnah meaning and further study should be focused on Arabic language skills among deviant sects.